Technology Entrepreneurship : A Treatise on Entrepreneurs and Entrepreneurship for and in Technology Ventures. Band 1 - Runge, Wolfgang (KIT Scientific Publishing, 2013)
The treatise is the first coherent and comprehensive presentation of the important sub-field of ""technology entrepreneurship"" emphasizing the science and engineering perspectives. It is a presentation of technology entrepreneurship as an inter-cultural approach referring to the US and Germany. It integrates micro- and macro aspects referring to numerous cases of firms' foundations. The book provides also a new semi-quantitative approach to growth of new technology ventures.